AB1102-HPR "if A Joint Is Hot It's Not The Time": Health Professionals' Views on Developing Physical Activity Interventions for People Who Have Rheumatoid Arthritis. (15th July 2016) - Larkin, L.; Gallagher, S.; Fraser, A.; Kennedy, N.
Abstract : Background: Although numerous physical activity interventions exist for people who have RA sustaining physical activity levels after an intervention is completed has been challenging. Involving key stakeholders is important when designing complex interventions which target behaviour change [1]. Health professionals (HPs) working in rheumatology can provide unique views on the design of interventions and can highlight potential challenges/facilitators to a proposed intervention for people who have RA [2–3]. Objectives: This study aimed to explore the views of HPs on physical activity in people who have RA, and the design of a behaviour change intervention to promote physical activity participation amongst people who have RA. Methods: We used a qualitative methodology and constructivist approach. Interviews were conducted by phone, with the use of an interview guide. Interviews were transcribed and analysed using thematic analysis. The interview transcripts were read, notes made and ideas formulated to facilitate coding. The research team searched for patterns, analysed and coded the data, and generated sub-themes and themes. Themes were reviewed by the research team to check if the themes worked in relation to the coded extracts and the entire data set. Results: 14 interviews were conducted (rheumatologists n=7, physiotherapists n=4 and clinical nurse specialists n=3). Mean clinical practice experience was 15 years (range 3–34 years, SD ±8.76 years). Three key themes were generated: " Personal opinions", "Supporting physical activity " and `An ideal world' . Although HPs viewed physical activity as important, recommending it was largely based on a persons' disease status rather than empirical evidence. There was also a strong feeling that physical activity should reduce during a disease flare-up. Supporting physical activity in clinical practice was discussed as being through the provision of information, goal setting and behaviour monitoring. Having contact with a HP was also thought to support physical activity. The "ideal world" was discussed with resources being highlighted as a key challenge to interventions in clinical practice, e.g. lack of time, staff numbers. Some participants felt that a group setting was most feasible in clinical practice whilst others preferred a 1:1. Conclusions: HPs believe physical activity is important for people who have RA, although there is uncertainty regarding physical activity recommendations for this population. Thus there is scope to increase HPs' knowledge of recent evidence. Views varied on how an intervention to promote physical activity should be delivered but consideration of barriers to delivery in clinical practice is important. References: Medical Research Council (2008) Developing and evaluating complex interventions: new guidance. http://www.mrc.ac.uk/Utilities/Documentrecord/index.htm?d=MRC004871 . Brodin N et al (2015) Promotion of health-enhancing physical activity in rheumatoid arthritis: a comparative study on healthcare providers in Italy, The Netherlands and Sweden. Rheumatol Int 35(10):1665–73 Hurkmans EJ et al (2011) Promoting physical activity in patients with rheumatoid arthritis: rheumatologists' and health professionals' practice and educational needs. Clin Rheumatol 30:1603–1609 Disclosure of Interest: None declared